Resistance-associated mutations after initial antiretroviral treatment failure in a large cohort of patients infected with HIV-1 Subtype CRF01_AE - Praparattanapan,J. (Bentham Science Publishers B.V., 2015)
The nucleoside reverse transcriptase inhibitors (NRTIs), zidovudine (AZT) and stavudine (d4T) are thymidine analog drugs recommended as first-line antiretroviral therapy in HIV-1-naïve patients. Two thymidine analog mutation (TAM) pathways, TAM-1 and TAM-2, confer high levels of resistance with mutations in the viral RT. The relative prevalence of TAM pathways and their associations with other NRTI resistance mutations acquired under the pressure of drug treatment in a large cohort of 1,876 patients infected with HIV-1 CRF01_AE attending the Infectious Disease Clinic, Chiang Mai University Hospital, Chiang Mai, Thailand, were studied. From 117 patients infected with HIV-1 CRF01_AE who had plasma HIV-1 RNA of ≥500 copies/mL, 69 patients had at least one TAM. The most common mutation associated with NRTI resistance was M184V/I (89.9%). The TAM-2 (89.9%) pathway occurred approximately two times more frequently than the TAM-1 (43.5%) pathway. The presence of TAM and the TAM-1 pathway was significantly more frequent in the AZT- than the d4T-receiving group ((OR, 2.89; 95% CI, 1.12-7.46; P<0.05) and (OR, 3.33; 95% CI, 1.19-9.37; P<0.05), respectively). In conclusion, the TAM-2 pathway was selected more frequently than the TAM-1 pathway by thymidine analog drugs in HIV-1 CRF01_AE-infected patients, while the TAM-1 pathway occurred more frequently than the TAM-2 pathway in such patients with AZT-based treatment. Routine monitoring of plasma HIV-1 RNA may result in less exposure to failing regimens and reduce the opportunity for TAMs to accumulate. However, the low frequency of the TAM-1 pathway in our cohort data suggests that these patients should respond well to second-line regimens containing a ritonavir-boosted protease inhibitor. © 2012 Bentham Science Publishers.